Foodomics and storage monitoring of three meat cuts by 1H NMR. (26th April 2019) - Fontes, José Eraldo do Nascimento; Rodriguez‐Caturla, Magdevis Yanet; Sant'Ana, Anderson S.; Lopes, Thiago Inácio Barros; Marsaioli, Anita Jocelyne
Abstract: The growth of NMR foodomics is described in the context of a study of beef storage. Thirty samples of three meat cuts (chuck, sirloin, and tenderloin) were analyzed using 1 H NMR spectroscopy to determine the influence of storage period and temperature. 1 H showed signals belonging to metabolites namely: acetate, adenosine, adenine, ADP, alanine, betaine, creatine, creatinine, carnosine, fumarate, glycerol, glycine, glutamine, isoleucine, lactate, leucine, methionine, and valine. The score plots (PCA) separated the samples of different storage time, reflecting possible meat degradation. Samples of no storage time (time zero) were grouped in the PC1 and PC2 negatives axis. The score plots suggest that the temperature has a huge influence on the degradation extent and possible influences the growth of the microbial populations.